Performance Measurement of Syariah Complaint Stocks and Conventional Stocks in Kuala Lumpur Stock Exchange - Ali, Salman (2014)
This research provides an acute review on the performance and characteristics of Syariah compliant stocks and conventional stocks in Malaysia with main objectives of identifying and comparing the risk and return of both type of stocks. Performance is measured by using independent samples T-tests, Mann Whitney test and regression analysis to evaluate the relationship between the Syariah and conventional stocks returns of companies with their financial ratios. Using average weekly prices, the result shows that there is no statistical significant difference between the mean return and risk between both types of stocks. In addition, conventional stocks shows higher return with higher risk than Syariah complaint stocks. The regression shows that Earning per share and return on equity has significant relationship to stocks return of Syariah and conventional.